Distribution Characteristics and Influence Factors of Rhizosphere Glomalin-Related Soil Protein in Three Vegetation Types of Helan Mountain, China - Hou, Hui; Yan, Peixuan; Xie, Qinmi; Zhao, Hongliang; Zhang, Haiying; Lv, Yingze; Pang, Danbo; Hu, Yang; Li, Jingyao; Wang, Fang; Ni, Xilu (Forests, 2022)
To reveal distribution characteristics of glomalin-related soil protein (GRSP) and it’s influencing factors under different vegetation types in the drought-tolerant shrubland of Helan Mountain, we chose three vegetation types as study subjects: Stipa breviflora (Grassland, G), Amygdalus mongolica (Shrub, S), and Stipa breviflora-Amygdalus mongolica (Grassland-Shrub, G×S) and bare soil was used as the control (CK). The contents of easily extractable glomalin-related soil protein (EE-GRSP) and total glomalin-related soil protein (T-GRSP), soil physicochemical properties, colonization rate, spore density, and species abundance in the rhizosphere soil were determined. The results indicated that EE-GRSP and T-GRSP showed significant difference (p < 0.05) among vegetation types, with GRSP content highest under G×S (5.68 and 6.27 mg·g−1, respectively) and lowest under CK (3.84 and 4.48 mg·g−1, respectively). EE-GRSP/soil organic carbon (SOC) and T-GRSP/SOC showed no significant difference (p > 0.05). The trends of colonization rate, spore density, and species abundance were the same and were significantly different from those of GRSP content (p < 0.05), with maximum values of 75.6%, 20.7 × 10 g−1, and 29.7, and minimum values of 55.6%, 13.0 × 10 g−1, and 12.7, respectively. Pearson correlation analysis showed that EE-GRSP was significantly positively correlated with SOC, total phosphorus, available phosphorus, and colonization rate (p < 0.05), and it showed an extremely significant positive correlation with available potassium, spore density, and species abundance (p < 0.01). T-GRSP was significantly positively correlated with total phosphorus and available phosphorus (p < 0.05), as well as with soil organic carbon, available potassium, spore density, colonization rate, and species abundance (p < 0.01). The redundancy analysis (RDA) showed similar results. Therefore, the distribution characteristics of GRSP and its influencing factors under different vegetation types in the low elevation area of Helan Mountain were influenced by vegetation types, physicochemical properties of rhizosphere soil, and arbuscular mycorrhizal fungi (AMF) colonization, thus providing a scientific basis for soil quality improvement and vegetation restoration.